The Influence of Current Density on Transport of Vanadium Cations through Membranes with Different Charges. Issue 4 (7th April 2021) - Darling, Robert M.; Saraidaridis, James D.; Shovlin, Christopher; Fortin, Michael; Murdock, Laura A.; Benicewicz, Brian C.
Abstract : Fluxes of the four vanadium cations V 2+, V 3+, VO 2+ and VO2 + through three archetypal membranes were measured as functions of current density. The membranes include a cation-exchange membrane, an anion-exchange membrane, and an initially uncharged membrane. Comprehensive data sets including mass and vanadium sorption, in-plane and through-plane conductivity, diffusive permeability, and transference number were collected to help interpret vanadium fluxes. Conductivity, diffusion coefficient, and transference number appear to be inter-related as predicted by Nernst-Planck theory for the cation-exchange membrane Nafion. The properties do not appear to be as compellingly connected for the anion-exchange membrane FAPQ-330 or polybenzimidazole. The Nernst-Planck formalism, with the Nernst-Einstein approximation, predicts a larger influence of current density on vanadium flux than is observed experimentally for these membranes. Possible explanations for these disparate findings are investigated and discussed.